Comparison of meat quality parameters in surgical castrated versus vaccinated against gonadotrophin-releasing factor male and female Iberian pigs reared in free-ranging conditions. (January 2016) - Martinez-Macipe, M.; Rodríguez, P.; Izquierdo, M.; Gispert, M.; Manteca, X.; Mainau, E.; Hernández, F.I.; Claret, A.; Guerrero, L.; Dalmau, A.
Abstract: This study compared carcass and meat quality traits between 16 vaccinated (VF), 19 castrated (CF) and 8 entire (EF) female Iberian pigs, and between 21 vaccinated (VM) and 19 castrated (CM) male Iberian pigs reared in free ranging conditions. Vaccination consisted in the application of Improvac® at the age of 11, 12 and 14 months in VF and VM. Pigs were slaughtered at 16 months. In females, carcass and meat quality were found to be very similar regardless of the treatment. In males, VM had a leaner carcass, lower (P < 0.05) percentage of intramuscular fat, higher shear force and more rancidity than CM (P < 0.05 in all cases). It could be concluded that vaccination or castration had no major effects on quality traits in females. It should be then stated that entire females are suitable for free-range conditions in terms of product qualities. Vaccination in females did not alter carcass and meat quality, and specific interests should consider reproductive behavior in free-range conditions. Highlights: Meat quality traits did not differ between castrated, GnRF-vaccinated or entire females. Vaccination against GnRF produced a leaner carcass in males. Entire and GnRF-vaccinated males had large differences in sensory meat quality. Entire females are suitable for quality standards of Iberian pig production.